New optimized configuration for a hybrid PV/diesel/battery system based on coyote optimization algorithm: A case study for Hotan county. (November 2022) - Sari, Arif; Majdi, Ali; Opulencia, Maria Jade Catalan; Timoshin, Anton; Huy, Dinh Tran Ngoc; Trung, Nguyen Dinh; Alsaikhan, Fahad; Hammid, Ali Thaeer; Akhmedov, Abdulaziz
Abstract: The main objective of this study is to present a multi-objective and optimal hybrid PV/diesel generator/ battery Renewable Energy System (HRES) to provide this reliability in the Hotan county, placed in Taklamakan Desert. This study uses the ɛ -constraint method along with a developed version of the coyote optimization algorithm to achieve the best values of the component sized to decrease the loss of load probability, CO2 emission value, and the annualized cost of the system. Sensitivity analysis also is performed to show each component's impact on the system. The results demonstrate that the DG backup system improves the yearly cost of the system from 8347.2 $ to 9318.4 $, which shows about 10.42% increasing by increasing the fuel consumption. Here, the LLP increases from 0% to 9.19% and the CO2 emissions improve from 2531.2 kg/yr to 13257 kg/yr. Accordingly, the COE value is reduced from 0.39 $/kWh to 0.24 $/kWh over the PV penetration, reducing from 92.27% to 59.42%. This decreasing indicates that the system fuel cost has more impact than the cost of PV on the COE, which is due to the low cost required of conventional power production than the PV system. The results also indicate a noteworthy upshot on the battery storage unit size such that the size of ɛ C O 2 has been enhanced from 27.4 kWh to 50 kWh in the range from 7000 kg/year to 25 kg/year. The results also are compared with the PSO-based optimal system and HOMER software results to show its excellence toward them. Highlights: Multi-objective reliable optimization of HRES in Hotan county. Using ɛ -constraint method for simplifying the multi-objective optimization. A developed version of the coyote optimizer for optimization of the problem. The purpose is to decrease the LLP, CO2 emission, and the annualized cost of the system. Investigation of the method based on sensitivity analysis.